(480) General Consideration of Educational Planning - A. Zaki (معهد التخطيط القومى, 2026)
This study examines educational planning as a fundamental component of comprehensive national planning and argues that education should no longer be viewed as an isolated social service but rather as a strategic instrument directly linked to socio-economic development. The study is based on the assumption that effective development requires systematic utilization of human, material, scientific, and technological resources within a framework of clearly defined national objectives. The study explains that educational planning can be approached from two major perspectives. The first concerns planning the educational process itself, including school facilities, curricula, teachers, instructional resources, educational stages, and evaluation systems. The second concerns the role of education within the broader national development framework and its contribution to economic and social goals. The study emphasizes that education both reflects and shapes the social and political characteristics of the state. The paper further argues that underdevelopment is not caused by a single factor but results from the interaction of poverty, ignorance, disease, unemployment, and poor living conditions. These factors restrict human productivity and reduce individuals’ creative capacities, making systematic planning essential for development. The study notes that planning became increasingly important after World War II, particularly among newly independent countries in Asia and Africa seeking rapid social and economic advancement. The study emphasizes that improving living standards requires increasing productivity and efficiency, which can be achieved through education, learning, and training. Education is therefore considered an investment in human capital rather than merely a governmental expenditure or a social service. The study also stresses the importance of aligning educational outputs with labor-market requirements and estimating future manpower needs across economic sectors. The study concludes that educational planning serves as a cornerstone of national socio-economic planning and that sustainable development depends largely on preparing qualified human resources capable of utilizing available resources effectively and contributing to long-term national progress.